Active surveillance in younger patients with prostate cancer: clinical characteristics including longitudinal patient-reported outcomes. (29th December 2022) - Tohi, Yoichiro; Kato, Takuma; Matsuda, Iori; Honda, Tomoko; Osaki, Yu; Naito, Hirohito; Matsuoka, Yuki; Okazoe, Homare; Taoka, Rikiya; Ueda, Nobufumi; Sugimoto, Mikio
Abstract: Objective: this study aimed to evaluate the active surveillance continuation period, treatment intervention rate and health-related quality of life in younger patients. Methods: we prospectively conducted a health-related quality of life survey of patients enrolled in the Prostate Cancer Research International: Active Surveillance-JAPAN study at Kagawa University between January 2010 and December 2020. Health-related quality of life was assessed by mail using a validated Japanese version of the Short-Form 8 Health Survey and Expanded Prostate Cancer Index at active surveillance enrolment and annually thereafter until discontinuation of active surveillance. We divided the patients into two groups, younger (aged <65 years) and older (aged ≥65 years), and compared the two groups. Results: of the 84 patients, 22 were in the younger group. The active surveillance continuation period was shorter in the younger group than in the older group. The 3-year treatment intervention rate was higher in the younger group than in the older group. The majority of the reasons for definitive treatment were related to the protocol, which was similar in both groups (80 versus 76%). The sexual summary scores at active surveillance enrolment were higher in the younger group than in the older group. During active surveillance, the younger group and the older group showed no deterioration in all health-related quality of life scores compared with the scores at the enrolment of active surveillance. Conclusions: patient-reported health-related quality of life survey indicated that the health-related quality of life of younger Japanese patients was maintained over time during active surveillance, similar to that of older patients. Abstract : During active surveillance, the health-related quality of life of younger Japanese patients was maintained over time, and the surveillance period was shorter in younger patients compared with older patients.